The BIR2/BIR3-Associated Phospholipase Dγ1 Negatively Regulates Plant Immunity . Issue 1 (9th March 2020) - Schlöffel, Maria A.; Salzer, Andrea; Wan, Wei-Lin; van Wijk, Ringo; Del Corvo, Raffaele; Šemanjski, Maja; Symeonidi, Efthymia; Slaby, Peter; Kilian, Joachim; Maček, Boris; Munnik, Teun; Gust, Andrea A.
Abstract : A phospholipase D is a negative regulator of plant immunity and forms complexes with regulatory receptor-like kinases. Abstract: Plants have evolved effective strategies to defend themselves against pathogen invasion. Starting from the plasma membrane with the recognition of microbe-associated molecular patterns (MAMPs) via pattern recognition receptors, internal cellular signaling pathways are induced to ultimately fend off the attack. Phospholipase D (PLD) hydrolyzes membrane phospholipids to produce phosphatidic acid (PA), which has been proposed to play a second messenger role in immunity. The Arabidopsis ( Arabidopsis thaliana ) PLD family consists of 12 members, and for some of these, a specific function in resistance toward a subset of pathogens has been shown. We demonstrate here that Arabidopsis PLDγ1, but not its close homologs PLDγ2 and PLDγ3, is specifically involved in plant immunity. Genetic inactivation of PLDγ1 resulted in increased resistance toward the virulent bacterium Pseudomonas syringae pv. tomato DC3000 and the necrotrophic fungus Botrytis cinerea . As pldγ1 mutant plants responded with elevated levels of reactive oxygen species to MAMP treatment, a negative regulatory function for this PLD isoform is proposed. Importantly, PA levels in pldγ1 mutants were not affected compared to stressed wild-type plants, suggesting that alterations in PA levels are not likely the cause for the enhanced immunity in the pldγ1 line. Instead, the plasma-membrane-attached PLDγ1 protein colocalized and associated with the BAK1-INTERACTING RECEPTOR-LIKE KINASES BIR2 and BIR3, which are known negative regulators of pattern-triggered immunity. Moreover, complex formation of PLDγ1 and BIR2 was further promoted upon MAMP treatment. Hence, we propose that PLDγ1 acts as a negative regulator of plant immune responses in complex with immunity-related proteins BIR2 and BIR3.